Measuring Innovation Potential in Ecuadorian ICT Companies: Development and Application of the CRI-IRT Model - Christian Anasi; Andrés Robalino-López; Verónica Morales; Carlos Almeida (Information)
Innovation is recognized as a key source of competitive advantage for organizations and a driver of societal well-being. Therefore, managing and quantifying innovation is necessary to fully leverage its potential. Although many innovation measurement tools exist, contextual differences limit their applicability, highlighting the need for tools tailored to regional and national specificities. This study aimed to develop a measurement tool for the Ecuadorian context, utilizing the Capacities, Results, and Impacts (CRI) model questionnaire for data collection and Item Response Theory (IRT) as a processing method. The CRI model offers a comprehensive framework for assessing innovation potential, enabling a dynamic understanding of this potential while highlighting nuances specific to regional contexts, particularly in Ecuador. Complementing this, IRT—a statistical framework for measuring latent traits—offers several advantages over classical methodologies, such as Classical Test Theory (CTT) and simple aggregate scoring methods. Unlike classical approaches, which often lack precision at extreme ability levels and are heavily sample-dependent, IRT provides item-level analysis, ensures parameter invariance across samples, and maintains accuracy across a wide range of latent trait levels. Together, these methodologies ensure a highly reliable and context-specific innovation measurement tool. Six IRT models were fitted using data from a national multisector sample of 321 organizations, providing a multidimensional measurement scale specialized in measuring innovation potential in Ecuador. These scales were later applied in a case study on the Information and Communication Technology (ICT) sector in Quito, Ecuador. The findings showed that ICT organizations had higher innovation potential than other industries in Ecuador but faced weaknesses in areas like access to funding. Based on these results, targeted strategies were proposed to address these weaknesses and foster innovation within the ICT sector. This research contributes to the field of managing innovation in Ecuador and the broader Latin American region by developing a context-specific and adaptable tool to benchmark innovation, guide organizational strategies, and shape public policy. While the ICT sector was identified as a key driver for addressing Ecuador’s innovation challenges, this research provides valuable contributions toward tackling these challenges and fostering innovation in the country.